The global and the local : diverse perspectives in comparative education. - Astiz, M. Fernanda; Akiba, Motoko (WCCES series ;, 2016)
The book examines how the understanding of the global and the local has changed in response to ongoing reconfigurations between the state and society. It also emphasizes the importance of schooling as an institution both within and across national contexts, a holistic approach that helps us move beyond a conglomeration of isolated local events to pay attention to global trends. In this regard, the book underscores the richness of contextual factors that may create opportunities for innovation, or may serve as constraints in the implementation process. As a whole, the book brings new questions about globalization and the imperatives of education policy and implementation.